MANFAAT PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT DI WILAYAH KECAMATAN PEDAN KABUPATEN KLATEN - Agus Purwanto (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2016)
The objectives of this research were (1) To determine the benefits of community development / local institutions that have been implemented by the government (2) To determine the assistance that has been done by the government of businessmen-small entrepreneurs in Sub district Pedan (3) To determine the skill level of the community before and after the training conducted by the government through the PNPM program (4) To determine differences in the welfare of people in the District Pedan before and after there is direct assistance by government funds through PNPM program. Â This research was conducted in the District of Klaten sub district Pedan. By taking a sample of 40 respondents. Data analysis technique using different test and Benefit Cost Ratio (B/C Ratio). Â The research found that there is a difference between before and after the implementation of the PNPM program on community empowerment, mentoring, training, and direct grants. PNPM program is effective because it can increase empowerment, mentoring, training and financial assistance loans to the public, so concluded is helpful. Â Keywords: empowerment, mentoring, training, grants, PNPM